Biomechanical Analysis of Capsular Repair Versus Arthrex TFCC Ulnar Tunnel Repair for Triangular Fibrocartilage Complex Tears. (July 2019) - Johnson, Jayson C.; Pfeiffer, Ferris M.; Jouret, Jill E.; Brogan, David M.
Background: This study compares the effectiveness of a peripheral capsular repair with a knotless arthroscopic transosseous ulnar tunnel repair (TR) in restoring distal radioulnar joint (DRUJ) stability and stiffness in the setting of a massive triangular fibrocartilage complex (TFCC) tear.Methods: Eight matched pairs of fresh-frozen cadaveric forearms were tested. Each forearm was tested in supination and pronation using 3-dimensional (3D) optical tracking devices prior to any intervention. Each specimen then underwent a diagnostic wrist arthroscopy and sectioning of the TFCC's deep and superficial fibers. All specimens were then retested to assess instability secondary to the tear. The TFCC was repaired with either a peripheral capsular repair (CR) using three 2-0 polydioxanone sutures or a transosseous ulnar TR using a 2-0 FiberWire, and then retested (statistical significance; P < .05).Results: After TFCC arthroscopic sectioning, all specimens were unstable with a significant increase in translation and a significant decrease in stiffness. TFCC repair with TR resulted in displacement and stiffness similar to the native tissue. CR specimens were found to have significantly greater displacement and significantly decreased stiffness compared with the intact state.Conclusions: Arthroscopic sectioning of the TFCC resulted in DRUJ instability, as measured by stiffness and ulnar translation. TR effectively restored DRUJ stability and demonstrated no significant difference in postoperative stiffness or maximal displacement when compared with the intact specimen in pronation and supination. This study provides biomechanical evidence that an arthroscopic ulnar tunnel technique can restore stability to the DRUJ after a massive TFCC tear.